Analisa Mikrosatelit dalam Bioteknologi Reproduksi Ternak (Suatu Kajian Pustaka) - Siti Darodjah Rasad (Jurnal Agripet, 2009)
Microsatellite analysis in biotechnology of animal reproduction (A Review)ABSTRACT. In year 1970 was found nucleotide sequence which have repeated sequence of nucleotide. with high polymorh and using PCR could be amplified. That sequenz of nucleotide called Microsatelite. Microsatelite consist of 1 6 repeated nucleotide, which is CA repeated as mostly a repeated DNA in the animal (Tautz and Renz, 1984). Based on difference of long and amount of repeated nucleotide, there are three kind of DNA satelite, midi-, mini- and microsatelite (Matiat and Vergmaud, 1982). Microsatelite analysis was used to analyze of paternity and identity of animal, which was done as a conventional analysis with blood group analysis. The advantage of microsatelite analysis compare to blood group system are the exclution probability was high (EXP 99.9%), needs small sampel (tissues, sperm or follicel of hair), could be use for all animal without special age and possible for died animal.